The European Union and China in Africa: A statistical review of trade relations in 2023 - (:unkn) unknown (My University, 2024)
This working paper proposes an extraction of the most recent statistical data (updated on 31 July 2024 on the UNCTAD website) to illustrate the role played by the European Union on the African continent. Has the growth in trade been slower as a result of competition from China, or has it been sustained precisely by the arrival of Chinese companies? This paper will not attempt to answer this question, but will instead seek to provide an overview of China's and the EU's trade relations with Africa at the end of 2023.Two conclusions may be drawn from the aforementioned data. The first is the irrefutable influence of the European Union in Africa. It must be acknowledged that the European Union is not a homogeneous entity and therefore cannot be compared directly with any one country. However, this balance sheet demonstrates the interest in comparing China's role with that of the European Union, rather than with that of France or any other former European colonial power. Secondly, the significance of the five countries of Mediterranean Africa, both for China and for the countries of the European Union, further reinforces the necessity to consider the region in a European context. The countries bordering the Mediterranean Sea share a geographical and historical proximity to each other that they will never have with China.
Keywords: African Research